Does Dental Insurance Make a Difference in Type of Service Received by Iranian Dentate Adults? - Bayat, Fariborz; Murtomaa, Heikki; Vehkalahti, M Miira; Tala, Heikki; Mautsch, Walter (European journal of dentistry, 2011)
ABSTRACT Objectives: To assess the relationship between insurance status and type of service received among dentate adults in a developing oral health care system. Methods: A cross-sectional survey based on phone interviews in Tehran, Iran. Four trained interviewers collected data using a structured questionnaire. Of 1,531 subjects answering the phone call, 224 were <18 years; of the remaining 1,307, 221 (17%) refused to participate, and 85 (6%) were excluded as edentate or reporting no dental visit, leaving 1,001 eligible subjects in the sample. The questionnaire covered insurance status, socio-demographics, frequency of tooth brushing, dental attendance as reasons for, and time since last dental visit, and dental service received then. Data analysis included the chi-square test and logistic regression. Results: Of the subjects, 71% had a dental insurance. Those with no insurance were more likely to report tooth extractions (OR=1.5) than those with an insurance coverage; for all other treatments no differences according to the insurance status appeared. Among the insured subjects, extractions were more likely for those reporting a problem-based dental visit (OR=6.0) or having a low level of education (OR=2.3). Conclusions: In Iran, with its developing oral health care system, dental insurance had only a minor impact on dental services reported. (Eur J Dent 2011;5:68-76)